2019
DOI: 10.1073/pnas.1904410116
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the concepts cause, cost, and goal in prereaching infants

Abstract: We investigated the origins and interrelations of causal knowledge and knowledge of agency in 3-month-old infants, who cannot yet effect changes in the world by reaching for, grasping, and picking up objects. Across 5 experiments, n = 152 prereaching infants viewed object-directed reaches that varied in efficiency (following the shortest physically possible path vs. a longer path), goal (lifting an object vs. causing a change in its state), and causal structure (action on contact vs. action at a distance and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 64 publications
2
73
0
Order By: Relevance
“…We found general similarity between event representations in high-level regions of adults and infants, which can perhaps be understood in light of the sensitivity of infants to goal-directed actions and events (Levine et al, 2019). Young infants both predict the outcomes of actions (Woodward, 1998) and are surprised by ineffcient paths towards a goal (Liu et al, 2019) when a causal agent is involved. Unambiguous agency also increases the ability of older infants to learn statistical structure (Monroy et al, 2017), suggesting that the infant mind may prioritize agency.…”
Section: Discussionmentioning
confidence: 99%
“…We found general similarity between event representations in high-level regions of adults and infants, which can perhaps be understood in light of the sensitivity of infants to goal-directed actions and events (Levine et al, 2019). Young infants both predict the outcomes of actions (Woodward, 1998) and are surprised by ineffcient paths towards a goal (Liu et al, 2019) when a causal agent is involved. Unambiguous agency also increases the ability of older infants to learn statistical structure (Monroy et al, 2017), suggesting that the infant mind may prioritize agency.…”
Section: Discussionmentioning
confidence: 99%
“…Woodward (2000) suggested that it is the understanding of relational structure of actions that provides infants with word-world mappings. From early on, infants appreciate that objectdirected actions express meaningful relations between agents and the targeted objects (e.g., Woodward, 1998Woodward, , 1999Skerry et al, 2013;Liu et al, 2019). Hence, action analysis could serve as a filter for potential referents.…”
Section: Discussionmentioning
confidence: 99%
“…One example is the notion of causality (Michotte, 1963): causation is understood in infancy both in the physical (collisions) and in the social domain (goals) even before infants are able to reach (Liu et al, 2019). However, understanding mental causation, that is, conceiving and explaining the behavior of others as driven by intentions, beliefs and desires, an ability often called mentalization, is a piecemeal process.…”
Section: The Cognitive Capacities Underlying Folk Epistemologymentioning
confidence: 99%